An Analysis of Deixis in The Song Lyrics "Dear No One" by Tori Kelly - Rumbay, Lyvia Lauren; Liando, Nihta V F; Posumah, Jenie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The aim of this research is to analyze the three types of deixis found in the song lyrics “Dear No One” by Tori Kelly. It was conducted in order to examine the types of deixis revealed in the song lyrics “Dear No One” by Tori Kelly. Descriptive qualitative method were used in conducting this research. The data were collected through listening and analyzing the song “Dear No One” by Tori Kelly. The data were analyzed by the steps of data reduction, data display and drawing conclusion. After conducting the research, the findings of this research showed that the three types of deixis occurred in the song lyrics “Dear No One” by Tori Kelly. There were 37 data of deixis which are divided into; 30 data of person deixis that referred to person, 2 data of spatial deixis that referred to place, and 5 data of temporal deixis that referred to time.